Issues of the Russian liquefied natural gas market in the context of sanctions pressure and ways to solve them - A. A. Laznik; T. S. Gordeeva (Вестник университета)
Liquefied natural gas export is currently a rather promising sector of the Russian fuel and energy complex. Gas transportation by special gas carriers makes it possible to supply the resource independently of the pipeline system. In recent years, the liquefied natural gas market role has been significant for the Russian economy. This industry has not been subject to significant export restrictions by other countries, unlike pipeline gas exports. However, under the conditions of sanctions imposed by “unfriendly” countries on the supply of technologies and equipment required for liquefied natural gas production and transportation, not only the industry development, but also implementation of the Energy Strategy of the Russian Federation for the period up to 2035 is threatened, especially major projects implementation on the Arctic coast of the country. All of the above speaks for the relevance of the study, the objectives of which are to assess the Russian market of liquefied natural gas in the context of the introduced technological restrictions, to identify the key problems arising as a result of this unfavorable situation and to determine the directions for the industry further development.